2018
DOI: 10.4314/jfas.v9i6s.72
|View full text |Cite
|
Sign up to set email alerts
|

Persuasive technology as an intervention programs for Health care in Malaysia: a review

Abstract: The statistics regarding health problem in Malaysia shows more than 50% of Malaysian adults have at least one of Non-Communicable Disease. Thus, effort to create awareness as well as promoting mind-set change with regards to health habit is paramount. Researches prove that ICT played significant role in influencing the way of thinking, behaviour and decision making. Intervention programs through computer application should be used to persuade and support health awareness, treatment and prevention. This paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…When used at the right time, persuasion technology can encourage behaviour change (Fogg, 2003). Information, Communication and Technology (ICT) applications of persuasive technology played a significant role in influencing people's thinking, behaviour, and decision-making, which had a positive impact on raising awareness, assisting with prevention and support for change, and persuading people to lead healthier lives (Aziz et al, 2017).…”
Section: Healthcare Persuasive Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…When used at the right time, persuasion technology can encourage behaviour change (Fogg, 2003). Information, Communication and Technology (ICT) applications of persuasive technology played a significant role in influencing people's thinking, behaviour, and decision-making, which had a positive impact on raising awareness, assisting with prevention and support for change, and persuading people to lead healthier lives (Aziz et al, 2017).…”
Section: Healthcare Persuasive Technologymentioning
confidence: 99%
“…In recent years, PT has been used in several areas that directly or indirectly affect health and behaviour modification. Almonani, Husain, San, Almomani, & Al-Betar, 2014, have found that there are two main subfields of PT: illness management and prevention (Aziz, Salleh, Yusof, & Roseli, 2017) and health management and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are also aware that information and communication technology (ICT) plays a crucial role in affecting an individual's thinking, behaviour and decision making (Aziz et al, 2017). Therefore, researchers intend to use SM as the main medium of PT to influence as many people while exploiting the effectiveness of social influence.…”
Section: Persuasive Technologymentioning
confidence: 99%
“…In the last ten years, PT has been used in various fields impacting one or more aspects of health and behaviour change. Researchers have summarized two main areas of PT, which are (1) health management and prevention (Almonani, Husain, San, Almomani, & Al-Betar, 2014) and (2) disease management (Aziz, Salleh, Yusof, & Roseli, 2017).…”
Section: Introductionmentioning
confidence: 99%